Dot enzyme‐linked immunosorbent assay strip as a screening tool for detection of autoantibody to interferon gamma in sera of suspected cases of adult‐onset immunodeficiency. Issue 7 (22nd April 2018) - Rattanathammethee, Kritsadee; Chawansuntati, Kriangkrai; Chaiwarith, Romanee; Praparattanapan, Jutarat; Supparatpinyo, Khuanchai; Wipasa, Jiraprapa
Abstract : Background: Being able to detect the presence of autoantibodies to interferon (IFN)‐γ in serum is essential for evaluating patients with suspected adult‐onset immunodeficiency (AOID) with unusual intracellular infections. Most reported patients with AOID have been Asian, although the exact prevalence of this illness is unknown. To date, no standard assay exists to detect autoantibodies to IFN‐γ. An easy‐to‐use, low‐cost assay that can be performed in any laboratory would be a valuable tool for clinical management of AOID, as well as better reveal its prevalence. Methods: Our experimental study exploited a dot enzyme‐linked immunosorbent assay (Dot‐ELISA) strip to detect autoantibodies to IFN‐γ. Sera from 66 HIV‐negative patients having autoantibodies to IFN‐γ as determined by indirect ELISA were tested. Results: Dot enzyme‐linked immunosorbent assay was sensitive (100%) and specific (94.5%), with a positive predictive value of 97.6% and a negative predictive value of 100%. Conclusion: This simple method provides prompt qualitative results that can be read visually and used in facilities with limited testing capabilities.